Analisa Dampak Program Pemberdayaan Ekonomi Kampung Edamame Melalui Pelaku UMKM Edamame Krispi Mitra PT Gading Mas Indonesia Teguh (GMIT) - Gesti Setyo Hadi; Alvina Setiyawati; Ayu Firza Novianti (Lembaga Pengembangan Kinerja Dosen, 2024)
Jember is one of the regions that produces Edamame soybeans. The community empowerment through the Edamame Village has become an encouragement for economic development, especially for the people of Curah Kates Village. By utilizing the remaining materials from Edamame soybean sorting into an economically valuable product. This study aims to deeply analyze the impact of the empowerment program on the economy of the Curah Kates village community through the MSME actors of the Edamame Village who collaborate with PT Gading Mas Indonesia Teguh (GMIT). The empowerment program carried out by the Edamame Village has a significant impact on employment, income, and women's empowerment. The economic empowerment program of Curah Kates Village through the Edamame Village is one form of the implementation of the corporate social responsibility (CSR) program of PT Gading Mas Indonesia Teguh. In this program, the company is obligated to be responsible for the social and environmental impacts generated by the company's operations. This research uses a Qualitative method, this method is used to deepen the research conducted. The data collection techniques used in this study were carried out through observation and in-depth interviews with the research subjects.